Evaluating the effects of sedentary behaviour on plantar skin health in people with diabetes. Issue 4 (November 2020) - Henshaw, F.R.; Bostan, L.E.; Worsley, P.R.; Bader, D.L.
Abstract: Background: Diabetes-Related Foot Ulcers (DRFUs) are a common and devastating consequence of Diabetes Mellitus and are associated with high morbidity, mortality, social and economic costs. Whilst peak plantar pressures during gait are implicated cited as a major contributory factor, DRFU occurrence has also been associated with increased periods of sedentary behaviour. The present study was designed aimed to assess the effects of sitting postures on plantar tissue health. Methods: After a period of acclimatisation, transcutaneous oxygen tensions (TC PO2 ) and inflammatory cytokines (IL-1α and IL-1RA) were measured at the dorsal and plantar aspects of the forefoot before, during and after a 20-min period of seated-weight-bearing in participants with diabetes (n = 11) and no diabetes (n = 10). Corresponding interface pressures at the plantar site were also measured. Results: During weight-bearing, participants with diabetes showed increases in tissue ischaemia which were linearly correlated proportional to plantar pressures (Pearson's r = 0.81; p < 0.05). Within the healthy group, no such correlation was evident (p > 0.05). There were also significant increases in post seated weight-bearing values for ratio for IL-1α and IL-1RA, normalised to total protein, post seated weight-bearing in participants with diabetes compared to healthy controls. Conclusion: This study shows that prolonged sitting may be detrimental to plantar skin health. It highlights the need to further examine the effects of prolonged sitting in individuals, who may have a reduced tolerance to loading in the plantar skin and soft tissues. Highlights: Peak plantar pressures during gait contribute to diabetes related foot ulcers. Sedentary behaviour is also associated with ulceration. Significant increases in ratio for IL-1α and IL-1RA were observed post seated weight-bearing in participants with diabetes compared to controls. Prolonged sitting may cause local plantar tissue ischemia in individuals with diabetes but not in healthy control participants. A high degree of variability in each of the output parameters was reported in both cohorts. This could be attributed to comorbidities or medication. Further studies are warranted to examine the effects of prolonged sitting in individuals with diabetes who may have a reduced tolerance to loading.